2021
DOI: 10.1101/2021.05.06.21256741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histopathological Image Analysis for Oral Squamous Cell Carcinoma classification using concatenated deep learning models

Abstract: Oral squamous cell carcinoma (OSCC) is a subset of head and neck squamous cell carcinoma (HNSCC), the 7th most common cancer worldwide, and accounts for more than 90% of oral malignancies. Early detection of OSCC is essential for effective treatment and reducing the mortality rate. However, the gold standard method of microscopy-based histopathological investigation is often challenging, time-consuming and relies on human expertise. Automated analysis of oral biopsy images can aid the histopathologists in perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In order to highlight the enhanced performance of ISMA-AIOCC technique, a comparison study was conducted and the results are shown in Fig. 12 [21]. The experimental results indicate that Visual Geometry Group (VGG16) and Support Vector Machine (SVM) models obtained the least classification performance.…”
Section: Resultsmentioning
confidence: 99%
“…In order to highlight the enhanced performance of ISMA-AIOCC technique, a comparison study was conducted and the results are shown in Fig. 12 [21]. The experimental results indicate that Visual Geometry Group (VGG16) and Support Vector Machine (SVM) models obtained the least classification performance.…”
Section: Resultsmentioning
confidence: 99%
“…Ibrar et al [ 6 ] presented conversion learning based on adapting deep learning to diagnose histopathological images to diagnose OSCC. They extracted and categorized deep features using three CNN models; the models achieved an accuracy of 89.16% with VGG16.…”
Section: Related Workmentioning
confidence: 99%
“… Comparison of the performance of our system with previous studies for diagnosing oral squamous cell carcinomas [ 6 , 10 , 16 , 37 , 38 , 39 ]. …”
Section: Figurementioning
confidence: 99%
“…And the number of operations that corresponds to it is equation (6). The total number of weights in depthwise separable convolution is equation ( 7), as well as the total number of operations in equation (8).…”
Section: Depthwise Separablementioning
confidence: 99%